1996
DOI: 10.1088/0960-1317/6/4/004
|View full text |Cite
|
Sign up to set email alerts
|

Surface micromachining by sacrificial aluminium etching

Abstract: Sacrificial aluminium etching enables micromechanical structures integrated with circuitry to be fabricated using standard IC processes followed by simple post-processing. In this paper, the etching characteristics of CMOS aluminium in four etch solutions are reported. The solutions are (A) a commercially available aluminium etchant, (B) Krumm etch, (C) diluted hydrochloric acid, and (D) diluted hydrochloric acid with hydrogen peroxide. The etching of narrow channels is studied as a function of time and temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 18 publications
3
32
0
Order By: Relevance
“…where A is the proportionality constant that accounts for molecular weight and density of the oxide layer; this equation takes the same form presented by Liu [46] and Westberg [47].…”
Section: Effect Of Silicon Microstructure Geometriesmentioning
confidence: 99%
“…where A is the proportionality constant that accounts for molecular weight and density of the oxide layer; this equation takes the same form presented by Liu [46] and Westberg [47].…”
Section: Effect Of Silicon Microstructure Geometriesmentioning
confidence: 99%
“…The first, Figure 20a uses the gate poly as the mechanical material and the second, Figure 20b, (Fedder, 1996) a combination of oxide and metal used in standard processes. An alternative approach is to use one of the aluminium layers as a sacrificial layer, and protecting the remaining aluminium layers with oxide (Westberg, 1996). The resulting structure is shown in Figure 21.…”
Section: Post-processingmentioning
confidence: 99%
“…More generally, we found that the presence of 0.1 equivalents of Ca 2 + in solution relative to the sum of all the monovalent cations was sufficient to maintain the insolubility of the PAA-Ca 2 + films. This approach did not, however, prove successful in very alkaline solutions, because the calcium ions precipitate in the form of Ca(OH) 2 , and could not be maintained at a sufficiently high concentration to maintain the ionic cross-linking of PAA. As a result, alkaline developers with pH values of 12-13 (such as the 351 developer used for Shipley positive photoresists) are currently not compatible with the PAA films.…”
Section: Modifying the Solubility Of Paa By Ion Exchangementioning
confidence: 99%
“…Although some non-silicate-based materials (e.g., titanium and aluminum) can be used as sacrificial layers with a HF etch, [2] the poor selectivity of this etch limits its usefulness with fragile materials, and its toxicity makes it inconvenient or hazardous for inexperienced users. HF-free etching solutions for aluminum are available, based on mixtures of acids and oxidants (i.e., concentrated phosphoric and nitric acids, hydrogen peroxide, and acetic acid), [2] but are also incompatible with some fragile materials. Porous silicon is also used for the fabrication of microsystems, and is coupled with a final dissolution in alkaline environment (KOH).…”
Section: Introductionmentioning
confidence: 99%